Clinical guides for atypical hemolytic uremic syndrome in Japan. Issue 7 (26th July 2016) - Kato, Hideki; Nangaku, Masaomi; Hataya, Hiroshi; Sawai, Toshihiro; Ashida, Akira; Fujimaru, Rika; Hidaka, Yoshihiko; Kaname, Shinya; Maruyama, Shoichi; Yasuda, Takashi; Yoshida, Yoko; Ito, Shuichi; et al.
Abstract: Atypical hemolytic uremic syndrome (aHUS) is a rare disease characterized by the triad of microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury. In 2013, we developed diagnostic criteria to enable early diagnosis and timely initiation of appropriate treatment for aHUS. Recent clinical and molecular findings have resulted in several proposed classifications and definitions of thrombotic microangiopathy and aHUS. Based on recent advances in this field and the emerging international consensus to exclude secondary TMAs from the definition of aHUS, we have redefined aHUS and proposed diagnostic algorithms, differential diagnosis, and therapeutic strategies for aHUS.